Strengthening Medication Taking Companion for Children's TB Patients with Media Kits - Ningtyias, Farida Wahyu; Prasetyowati, Irma; Nafikadini, Iken; Suandaru, Yusrizal Fatria (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2024)
Tuberculosis requires high adherence for its cure. Highly committed drug-taking assistants are needed to succeed in this process, hence the need to strengthen the cadres and families of TB patients, especially pediatric TB patients. This activity is in the form of education by using flipchart and flashcard media that can increase the effectiveness of message delivery. The target audience was cadres and parents of pediatric TB patients at Puskesmas Panti, Jember Regency on September 8, 2023. Evaluation of activities is carried out by measuring the level of knowledge and attitude changes using pre and post sheets. There was an increase in knowledge and positive attitude change of 1.75% and 3%. Media kits in the form of flipcharts and flashcards are effective for use during education/counseling